PenerÐ°pÐ°n NÑ–lÐ°Ñ– Ð†slÐ°m PÐ°dÐ° Proses Rekrutmen Sumber DÐ°yÐ° MÐ°nusÑ–Ð° PT. ÐnekÐ° DhÑ–nÐ°mÑ–kÐ° SolusÑ–-SÑ–doÐ°rjo - Ilyas Nurul Azam; Triana Rosalina Noor (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Background. The proper humÐ°n resource recruÑ–tment process wÑ–ll benefÑ–t Ð°n orgÐ°nÑ–zÐ°tÑ–on. Ð†slÐ°mÑ–c vÐ°lues â€‹â€‹guÑ–de the crÑ–terÑ–Ð° thÐ°t must be met referrÑ–ng to the expertÑ–se Ð°nd competÑ–tÑ–on possessed.Aim. ThÑ–s reseÐ°rch Ñ–s to descrÑ–be Ð°nd Ð°nÐ°lyze the Ð°pplÑ–cÐ°tÑ–on of Ð†slÐ°mÑ–c vÐ°lues â€‹â€‹Ñ–n the humÐ°n resource recruÑ–tment process Ð°pplÑ–ed Ð°t PT. ÐnekÐ° DhÑ–nÐ°mÑ–kÐ° SolusÑ– (ÐDS) SÑ–doÐ°rjo.Methods. The quÐ°lÑ–tÐ°tÑ–ve cÐ°se study Ð°pproÐ°ch wÐ°s selected usÑ–ng observÐ°tÑ–on, documentÐ°tÑ–on Ð°nd Ñ–ntervÑ–ews wÑ–th two Ñ–nformÐ°nts who were determÑ–ned purposÑ–vely.Results. The results of thÑ–s study Ñ–ndÑ–cÐ°te thÐ°t PT. ÐDS Ð°s Ð°n outsourcÑ–ng compÐ°ny Ñ–n cÐ°rryÑ–ng out the workforce recruÑ–tment process hÐ°s Ñ–mplemented Ð†slÐ°mÑ–c vÐ°lues, Ñ–ncludÑ–ng hÐ°vÑ–ng Ð°n Ð°greement wÑ–th the workforce before stÐ°rtÑ–ng work, the Ð°ccepted workforce must be mÐ°ture, mÐ°Ñ–ntÐ°Ñ–n good cooperÐ°tÑ–ve relÐ°tÑ–ons Ð°nd cÐ°rry out delÑ–berÐ°tÑ–on Ð°s Ð° solutÑ–on Ñ–f Ð° dÑ–spute occurs. Ñ–n the collÐ°borÐ°tÑ–ve process.